Embargo Terhadap Negara Dalam Keadaan Darurat Dan Pemenuhan Hak Asasi Manusia - Marthin Ellon Hattu; Popi Tuhulele; Richard Marsilio Waas (PATTIMURA Law Study Review, 2023)
An embargo is an international legal sanction in the form of prohibiting or restricting the import and export of goods or services between countries. This is triggered by conflicts made by a country where some embargo countries hope that this embargo policy can force other countries to want to jointly resolve conflicts that occur in a country that makes conflicts, The armed conflict that occurred in Syria under the Al-Assad regime caused many Syrians to be tortured and killed for demanding reforms, so that America and European Union countries implemented and imposed sanctions embargoes on the Syrian government. Article 41 of the Charter of the United Nations authorizes the UN Security Council to implement nonmilitary measures, including embargoes, in an effort to maintain or restore international peace and security. The purpose of this study is to analyze and determine the treatment of embargoes on countries in emergencies that can be qualified as violations and determine the legal impact of embargoes on the fulfillment of human rights, The research method used by the author is normative law using statutory, conceptual and case approaches. The results of this study show that the use of Embargo sanctions against countries in emergencies qualifies as a violation of human rights, because it can worsen the condition of civil society and also the embargo in an emergency has violated the provisions of international law in the Universal Declaration of Human Rights of 1948 which in that provision explains the inherent rights of human beings.